The Effect of Budget Participation on Managerial Performance with Organizational Commitment as Moderating Variable on Company: Pengaruh Partisipasi Anggaran terhadap Kinerja Manajerial dengan Komitmen Organisasi sebagai Variabel Moderating pada Perusahaan - Yanti, Leny Irma; Widodo, Heri (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of the study was to determine the effect of budgetary participation on managerial performance with organizational commitment as a moderating variable in the GAPENSI company. Companies that are members of the joint construction contractors in Sidoarjo are the population taken in this observation. The sample in this research was taken using a saturated sampling technique where the total sample population used in the questionnaire was 39 members of the GAPENSI company in Sidoarjo. The data analysis method used is Partial Least Square analysis. That the results of this study provide results, namely that the first budget participation affects managerial performance at the GAPENSI company, the second organizational commitment is not able to affect the relationship between budget participation and managerial performance at the GAPENSI company.